On A.D.Baratinsky and Her Translations from Thomas Moore’s “Irish Melodies” - Гончар-Ханджян, Наталия (Bulletin of Yerevan University H: Russian Philology, 2021)
The article presents A.D.Baratinsky (born Abamelek-Lazareva, 1814-1889), whose name enters into some pages of Russian poetry (poems of Pushkin, Kozlov, Vyazemsky etc.), whose activity in translation of Russian poet’s poems into English and European poet’s poems into Russian enters into the history of Russian literature, in particularly Russian versetranslation. The author examines in details the reasons of her choice from Thomas Moore’s “Irish Melodies”, as well as her artistic principles in the work of translation. The texts of Baratinsky are confronted with up-to-date translations of the same poems. The author when considering this poetic material broaches subjects of general meaning, especially the level of participation in translator’s work such components as psychology, aesthetics, techniques.
Keywords: Russian poets; romantic era; verse translation; Thomas Moore; Anna Baratinsky; personal motivation; self-expression